2009
DOI: 10.1016/j.bbamem.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the effect of detergents on the full-length rhomboid protease from Pseudomonas aeruginosa and its cytosolic domain

Abstract: Rhomboids comprise a family of intramembrane serine proteases that catalyze the cleavage of transmembrane segments within the lipid membrane to achieve a wide range of biological functions. A subset of bacterial rhomboids possesses an N-terminal cytosolic domain that appears to enhance proteolytic activity via an unknown mechanism. Structural analysis of a full-length rhomboid would provide new insights into this mechanism, an objective that solution NMR has the potential to realize. For this purpose we purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
4
15
1
Order By: Relevance
“…These domains are often large and conserved between rhomboid family members but are not essential for catalysis, suggesting a function in substrate recognition/specificity or regulation of activity (reviewed in [23]). Consistent with this hypothesis, the removal of the Nterminal cytosolic domain of RHBDL2 affects its activity in vitro [19] and the N-terminal domain of the Pseudomonas aeruginosa GlpG is also important for its function in vitro [25]. In the case of GlpG, Sherratt et al suggested that the N-terminus of the protease interacts with the catalytic core domain, enhancing its activity by altering the conformation/stability of the active site and/or aiding anchorage of the protease to the membrane [25].…”
Section: Cleavage Site and Substrate Recognitionsupporting
confidence: 60%
See 1 more Smart Citation
“…These domains are often large and conserved between rhomboid family members but are not essential for catalysis, suggesting a function in substrate recognition/specificity or regulation of activity (reviewed in [23]). Consistent with this hypothesis, the removal of the Nterminal cytosolic domain of RHBDL2 affects its activity in vitro [19] and the N-terminal domain of the Pseudomonas aeruginosa GlpG is also important for its function in vitro [25]. In the case of GlpG, Sherratt et al suggested that the N-terminus of the protease interacts with the catalytic core domain, enhancing its activity by altering the conformation/stability of the active site and/or aiding anchorage of the protease to the membrane [25].…”
Section: Cleavage Site and Substrate Recognitionsupporting
confidence: 60%
“…Consistent with this hypothesis, the removal of the Nterminal cytosolic domain of RHBDL2 affects its activity in vitro [19] and the N-terminal domain of the Pseudomonas aeruginosa GlpG is also important for its function in vitro [25]. In the case of GlpG, Sherratt et al suggested that the N-terminus of the protease interacts with the catalytic core domain, enhancing its activity by altering the conformation/stability of the active site and/or aiding anchorage of the protease to the membrane [25]. The iRhom family of pseudoproteases, which evolved from rhomboid proteases that lost their catalytic activity but retained their localization and the ability to bind their substrates, may provide additional regulatory functions.…”
Section: Cleavage Site and Substrate Recognitionsupporting
confidence: 60%
“…has been reported (21,35). Here, we see that the alkyl chain length does not have a significant effect on the rhomboid activity, unless the chains are very short compared with the natural E. coli phospholipids.…”
Section: Compoundsupporting
confidence: 50%
“…The rhomboid protein is an ancient conserved family of intramembrane serine proteases that catalyze the cleavage of transmembrane segments within the lipid membrane to achieve a wide range of biological functions (Sherrat et al, 2009). Recent reports have indicated that a subfamily of rhomboids are gatekeepers of mitochondrial dynamics and apoptosis, thus introducing a new paradigm of how the mitochondria uses these proteases to direct the stress responses, signal to the nucleus, and other key mitochondrial activities in health and disease (Hill and Pellegrini, 2010).…”
Section: Organelle-related Transcriptsmentioning
confidence: 99%